2011
DOI: 10.1039/c1dt10418g
|View full text |Cite
|
Sign up to set email alerts
|

Size-controlled synthesis of monodispersed mesoporous α-Alumina spheres by a template-free forced hydrolysis method

Abstract: We demonstrated the formation of monodispersed spherical aluminum hydrous oxide precursors with tunable sizes by controlling the variables of a forced hydrolysis method. The particle sizes of aluminum hydrous oxide precursors were strongly dependent on the molar ratio of the Al(3+) reactants (sulfates and nitrates). In addition, the systematic phase and morphological evolutions from aluminum hydrous oxide to γ-alumina (Al(2)O(3)) and finally to α-Al(2)O(3) through thermal dehydrogenation were characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The synthesis of the alumina particles was performed according to a slightly modified literature procedure [17]. Aluminum sulfate hexadecahydrate (2.00 g), aluminum nitrate nonahydrate (4.43 g), and urea (9.00 g) were dissolved in 2.0 L of deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of the alumina particles was performed according to a slightly modified literature procedure [17]. Aluminum sulfate hexadecahydrate (2.00 g), aluminum nitrate nonahydrate (4.43 g), and urea (9.00 g) were dissolved in 2.0 L of deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, γ-AlOHNPs, as prepared in this present study, are prone to decomposition. The weight loss (roughly 57.8%) at 1200°C corresponds to the removal of physisorbed (physically adsorbed) water as well as the further release of water accompanying phase transformation (γ-AlOOH → γ-Al 2 O 3 → α-Al 2 O 3 ) (Roh et al, 2011;Yue et al, 2011). Therefore, it can be understood that the porous nature of γand α-AlONPs originated from the thermal decomposition of γ-AlOHNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Three types of AlONPs were prepared by a modification of a previously described method (Roh et al, 2011). The starting materials were Al 2 (SO 4 ) 3 ·16H 2 O (purity 95%; Fluka), Al(NO3)3·9H2O (purity 98%; Sigma-Aldrich, St. Louis, MO, USA) and urea (extra pure; Orient Chemical Industry, Osaka, Japan).…”
Section: Preparation Of Alonpsmentioning
confidence: 99%
“…Very recently, it was reported that negative ions can affect crystal growth by controlling the morphology [25] and crystalline size [26][27][28]. For example, an anatase TiO 2 nanocrystals with a size of 20-150 nm was reported to be synthesized by changing the ratio of the anion concentration [26].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%